Feedback mechanisms stabilise degraded turf algal systems at a CO2 seep site - Ben P. Harvey (Nature Portfolio, 2021)
Ben Harvey et al. use the gradient provided by a natural CO2 seep off Shikine Island, Japan and lab microcosm experiments to determine how ocean acidification promotes turf algal habitat conditions that create stabilizing feedback loops and hysteresis capable of locking turf systems in place. These results further our understanding of feedback loops initiated by ocean acidification, and can assist in the management of coastal habitats.